Clinical characteristics and treatment experience of individuals with SCN8A developmental and epileptic encephalopathy (SCN8A-DEE): Findings from an online caregiver survey. (April 2022) - Cutts, Alison; Savoie, Hillary; Hammer, Michael F.; Schreiber, John; Grayson, Celene; Luzon, Constanza; Butterfield, Noam; Pimstone, Simon N.; Aycardi, Ernesto; Harden, Cynthia; Yonan, Chuck; Jen, Eric; et al.
Highlights: This is the first survey-based study of caregiver experiences in SCN8A-DEE. Caregivers report a broad range of seizure types and genetic variants in patients. Patients generally suffer from high seizure burden and multiple comorbidities. Results suggest new treatments and standardized treatment protocols are needed. Patient-centered research may improve awareness of SCN8A-DEE and patient outcomes. Abstract: Purpose: SCN8A developmental epileptic encephalopathy (SCN8A-DEE) is a rare and severe genetic epilepsy syndrome characterized by early-onset developmental delay, cognitive impairment, and intractable seizures. SCN8A gene variants are associated with a broad phenotypic spectrum and variable disease severity. A caregiver survey, solicited by the advocacy group The Cute Syndrome Foundation (TCSF), was conducted to gather information on the demographics/disease presentation, seizure history, and treatment of patients with SCN8A-related epilepsies. Methods: A 36-question online survey was developed to obtain de-identified data from caregivers of children with SCN8A-related epilepsy. The survey included questions on genetic diagnosis, disease manifestations/comorbidities, seizure severity/type, current/prior use of antiseizure medicines (ASMs), and best/worst treatments per caregiver perception. Results: In total, 116 survey responses (87 USA, 12 Canada, 12 UK, 5 Australia) were quantitatively analyzed. Generalized tonic/clonic was the most common seizure type at onset and time of survey; absence and partial/focal seizures were also common. Most patients (77%) were currently taking ≥2 ASMs; 50% had previously tried and stopped ≥4 ASMs. Sodium channel blockers (oxcarbazepine, phenytoin, lamotrigine) provided the best subjective seizure control and quality of life. Conclusion: The SCN8A-DEE patient population is heterogeneous in seizure characteristics and ASMs taken and is difficult to treat, with high seizure burden and multiple comorbidities. The high proportion of patients who previously tried and stopped ASMs indicates large unmet treatment need. Further collaboration between families, caregivers, patient advocates, clinicians, researchers, and industry can increase awareness and understanding of SCN8A-related epilepsies, improve clinical trial design, and potentially improve patient outcomes.